Penicillium janthinellum NCIM1366 shows improved biomass hydrolysis and a larger number of CAZymes with higher induction levels over Trichoderma reesei RUT-C30 - Sreeja-Raju, Athiraraj; Christopher, Meera; Kooloth-Valappil, Prajeesh; Kuni-Parambil, Rajasree; Gokhale, Digambar Vittal; Sankar, Meena; Abraham, Amith; Pandey, Ashok; Sukumaran, Rajeev K. (Biotechnology for Biofuels, 2020)
Background Major cost of bioethanol is attributed to enzymes employed in biomass hydrolysis. Biomass hydrolyzing enzymes are predominantly produced from the hyper-cellulolytic mutant filamentous fungus Trichoderma reesei RUT-C30. Several decades of research have failed to provide an industrial grade organism other than T. reesei, capable of producing higher titers of an effective synergistic biomass hydrolyzing enzyme cocktail. Penicillium janthinellum NCIM1366 was reported as a cellulase hyper producer and a potential alternative to T. reesei, but a comparison of their hydrolytic performance was seldom attempted. Results Hydrolysis of acid or alkali-pretreated rice straw using cellulase enzyme preparations from P. janthinellum and T. reesei indicated 37 and 43% higher glucose release, respectively, with P. janthinellum enzymes. A comparison of these fungi with respect to their secreted enzymes indicated that the crude enzyme preparation from P. janthinellum showed 28% higher overall cellulase activity. It also had an exceptional tenfold higher beta-glucosidase activity compared to that of T. reesei, leading to a lower cellobiose accumulation and thus alleviating the feedback inhibition. P. janthinellum secreted more number of proteins to the extracellular medium whose total concentration was 1.8-fold higher than T. reesei. Secretome analyses of the two fungi revealed higher number of CAZymes and a higher relative abundance of cellulases upon cellulose induction in the fungus. Conclusions The results revealed the ability of P. janthinellum for efficient biomass degradation through hyper cellulase production, and it outperformed the established industrial cellulase producer T. reesei in the hydrolysis experiments. A higher level of induction, larger number of secreted CAZymes and a high relative proportion of BGL to cellulases indicate the possible reasons for its performance advantage in biomass hydrolysis.
Keywords: Bioethanol; CAZymes; Cellulase; Penicillium janthinellum; Secretome; Trichoderma reesei

Early cellular events and potential regulators of cellulase induction in Penicillium janthinellum NCIM 1366 - Christopher, Meera; Sreeja-Raju, Athiraraj; Abraham, Amith; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Scientific Reports, 2023)
Cellulase production by fungi is tightly regulated in response to environmental cues, and understanding this mechanism is a key pre-requisite in the efforts to improve cellulase secretion. Based on UniProt descriptions of secreted Carbohydrate Active enZymes (CAZymes), 13 proteins of the cellulase hyper-producer Penicillium janthinellum NCIM 1366 (PJ-1366) were annotated as cellulases- 4 cellobiohydrolases (CBH), 7 endoglucanases (EG) and 2 beta glucosidases (BGL). Cellulase, xylanase, BGL and peroxidase activities were higher for cultures grown on a combination of cellulose and wheat bran, while EG was stimulated by disaccharides. Docking studies indicated that the most abundant BGL- Bgl2- has different binding sites for the substrate cellobiose and the product glucose, which helps to alleviate feedback inhibition, probably accounting for the low level of glucose tolerance exhibited. Out of the 758 transcription factors (TFs) differentially expressed on cellulose induction, 13 TFs were identified whose binding site frequencies on the promoter regions of the cellulases positively correlated with their abundance in the secretome. Further, correlation analysis of the transcriptional response of these regulators and TF-binding sites on their promoters indicated that cellulase expression is possibly preceded by up-regulation of 12 TFs and down-regulation of 16 TFs, which cumulatively regulate transcription, translation, nutrient metabolism and stress response.